2020
DOI: 10.3892/ijmm.2020.4654
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol may alleviate vascular inflammation in diabetic db/db mice

Abstract: Type 2 diabetes mellitus (T2dM) is associated with chronic low-grade inflammation. carvacrol has been confirmed to possess anti-inflammatory properties, but its effect on diabetic vasculature remains unknown. The aim of the present study was to investigate the possible protective effects of carvacrol against vascular endothelial inflammation. The mice were divided into four groups (n=15 per group) as follows: Non-diabetic control mice, db/db mice, db/db mice + carvacrol (low) and db/db mice + carvacrol (high) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The optical density values were determined using ImageJ software (version 1.48; National Institutes of Health). Furthermore, the semi-quantitative values of TNKS, AXIN2 and β-catenin expression were assessed via the percentage of positive cells (<5%, 0 point; 5–25%, 1 point; 26–50%, 2 points; 51–75%, 3 points and 76–100%, 4 points) and staining intensity (no staining, 0 point; light yellow, 1 point; brown, 2 points and tan, 3 points), as previously described ( 30 ). The product of the two was defined as follows: 0, negative (−) and >1 positive (+).…”
Section: Methodsmentioning
confidence: 99%
“…The optical density values were determined using ImageJ software (version 1.48; National Institutes of Health). Furthermore, the semi-quantitative values of TNKS, AXIN2 and β-catenin expression were assessed via the percentage of positive cells (<5%, 0 point; 5–25%, 1 point; 26–50%, 2 points; 51–75%, 3 points and 76–100%, 4 points) and staining intensity (no staining, 0 point; light yellow, 1 point; brown, 2 points and tan, 3 points), as previously described ( 30 ). The product of the two was defined as follows: 0, negative (−) and >1 positive (+).…”
Section: Methodsmentioning
confidence: 99%
“…Car/Thy reduce the activation of TLR4/NF-kB signaling pathway, whereas increase SOD1 and GSH antioxidants through Nrf2 Activation, attenuating oxidative damage (262,263). They suppress allergic inflammation associated with asthma Car/Thy downregulate miR-155, miR-146a, and miR-21 (264),.…”
Section: Carvacrol Thymolmentioning
confidence: 99%
“…Car and Thy reduce the activation of TLR4/NF-κB signaling pathway in vivo and in vitro in inflammatory reactions, whereas increase the expression of antioxidants, such as SOD1 and GSH through Nrf2 Activation and attenuates oxidative damage ( 262 , 263 ) ( Table 1 and Figure 1 ).…”
Section: Plant-derived Compounds Modulating the Tlr4/nf-κb Pathway Anmentioning
confidence: 99%
“…Through in-depth research, it has been revealed that numerous active ingredients in traditional Chinese medicine have the potential to relieve NAFLD. Increasing evidence has demonstrated that carvacrol (2-methyl-5-isopropylphenol), a monoterpenic phenol, may possess pharmacological properties, including neuroprotective ( 11 ), anti-inflammatory ( 12 ), anti-oxidative ( 13 ), anti-bacterial ( 14 ) and anti-cancer ( 15 ) effects. Carvacrol has been reported to relieve T2DM-related complications, such as vascular inflammation ( 12 ), hypercontractility in the aorta ( 16 ) and diabetic cardiomyopathy ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that carvacrol (2-methyl-5-isopropylphenol), a monoterpenic phenol, may possess pharmacological properties, including neuroprotective ( 11 ), anti-inflammatory ( 12 ), anti-oxidative ( 13 ), anti-bacterial ( 14 ) and anti-cancer ( 15 ) effects. Carvacrol has been reported to relieve T2DM-related complications, such as vascular inflammation ( 12 ), hypercontractility in the aorta ( 16 ) and diabetic cardiomyopathy ( 17 ). Nevertheless, to the best of our knowledge, the effect of carvacrol on T2DM-induced liver injury remains unknown.…”
Section: Introductionmentioning
confidence: 99%